Analisis Tren Penelitian Keterampilan Berpikir Kreatif dalam Pembelajaran IPA : Tinjauan Literatur Sistemik - Raudhah Maharana Fahmi; Jumadi Jumadi (Postgraduate, University of Mataram, 2023)
There are problems in science learning, such as decreased learning outcomes, a lack of student motivation, and difficult science material. This creative thinking skill is a solution to the problem. This study aims to provide information and alternative solutions using appropriate models or methods to improve creative thinking skills. The method employed is content analysis of articles from journals indexed by Sinta 1-2 from 2011 to 2023. The results of the study showed that the PBL and PJBL models were the right choice for implementing creative thinking skills by using science-based practicum material with the successful achievement of indicators of creative thinking skills, including indicators of flexibility and originality.